Traffic management during construction: case study of flyover at Jalan Bukit Ubi, Kuantan - Sharmaine, Shaari (2017)
Managing traffic at the construction area is the crucial part without having risks to health and safety whether it is in short or long term duration. Traffic management includes all physical measures designed to affect the movement of traffic on an existing network including the volume of traffic and the type of vehicles used. This paper present the implementation of traffic management during the construction of flyover at Jalan Bukit Ubi, Kuantan, Pahang. This paper study on what have been applied during the construction of flyover by the contractors, engineers and other construction worker. Also, there will be some changes of lanes, traffic flow etc, due to the construction of flyover. Besides, there will be some traffic congestion during the construction Therefore, traffic counting is conducted during and after the construction of flyover, which both are compared in terms of traffic volume and types of vehicles used. The problems occurred during and after the construction of flyover will be discussed further on this study.